2003
DOI: 10.1155/2003/729714
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Embolotherapy in Dieulafoy′s Disease of the Bronchus

Abstract: Dieulafoy's disease is a vascular anomaly characterized by the presence of a dysplastic artery that is related to an epithelial ulcer. The French surgeon Georges Dieulafoy first described it in 1898. Most frequently, it is a gastrointestinal condition, but occurrence in the bronchus has been reported in a few cases. The case of a 52-year-old man with massive hemoptysis, for which he underwent successful embolotherapy 10 years previously, is described. Over the next 10 years, he had several hospital admissions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 4 publications
(4 reference statements)
0
39
0
1
Order By: Relevance
“…Among the 12 cases of Dieulafoy's disease reported in the literature, five were described in smokers who had no associated comorbidity [22][23][24][25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Among the 12 cases of Dieulafoy's disease reported in the literature, five were described in smokers who had no associated comorbidity [22][23][24][25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…3 The characteristics of the lesion are nonspecific, but it can be suspected when a small (usually less than 1 cm) sessile non-pulsatile nodular lesion with a white cap and apparently normal mucosa is seen. 2 It has been suggested that, after the diagnosis has been made, angiography and embolization can be the preferred treatment 5,6 and that surgical resection would only be needed in a few cases. 4 However, the failure rate of embolization is not negligible, whereas surgery alone or after failure of embolization has had a success rate of nearly 100% in all reports.…”
Section: 3mentioning
confidence: 99%
“…In addition there is an almost simultaneous filling of the pulmonary artery branches of the affected area. 10 Histopathologic examination of the DL of the lung shows a dilated tortuous bronchial artery closely hugging the bronchus with infiltration of the bronchial wall and reaching immediately below the mucosal surface.…”
Section: Discussionmentioning
confidence: 99%
“…6 On the other hand, Bhatia et al reported the control of hemoptysis from a bronchial DL with repeated embolization over many years. 10 Undoubtedly, the nature and size of the vessels as well as the left-to-right shunt into the pulmonary arterial circulation make embolotherapy difficult in DL. However, in an otherwise stable patient, if a bronchial DL is suspected at the time of bronchial angiography, bronchial artery embolization should be performed.…”
Section: Discussionmentioning
confidence: 99%